NMDA receptor antibody in teratoma-related opsoclonus-myoclonus syndrome. (December 2018) - Urriola, Nicolás X.; Helou, Jacob; Maamary, Joel; Pogson, Jacob; Lee, Frederick; Parratt, Kaitlyn; Gillis, David; Fulham, Michael J.; Halmágyi, G. Michael
Highlights: NMDAR antibodies are infrequently found in opsoclonus-myoclonus syndrome (OMS). Diagnosis of OMS warrants evaluation for neuronal surface receptor autoantibodies, and exclusion of teratomas. Secondary (as yet unidentified) co-accompanying antibodies are likely needed to result in OMS. Abstract: Opsoclonus-myoclonus syndrome (OMS) is a brainstem/cerebellar syndrome producing disabling multi-directional saccadic oscillations with oscillopsia, with or without somatic myoclonus and cerebellar ataxia (Wong et al., 2001; Armangué et al., 2016). OMS is presumed to have an autoimmune basis and patients with it are tested for antineuronal antibodies and have imaging to locate any tumors. Here we report a unusual case of a young woman who had NMDAR antibody (NMDAR-ab) positive, teratoma-related, isolated OMS without encephalopathy. Removal of her ovarian teratoma, and immunotherapy with steroids, intravenous immunoglobulin (IVIg), plasma exchange (PLEX), and ultimately with B-cell depletion with rituximab resulted in total recovery after 3 months. Patients with teratoma-related OMS very rarely have NMDAR-ab which suggests that it is not the NMDAR-ab per se that causes the OMS.